Altered immune cell in human severe acute pancreatitis revealed by single-cell RNA sequencing - Wu, Zheyi; Wang, Shijie; Wu, Zhiheng; Tao, Junjie; Li, Lei; Zheng, Chuanming; Xu, Zhipeng; Du, Zhaohui; Zhao, Chengpu; Liang, Pengzhen; Xu, Aman; Wang, Zhenjie (Frontiers in Immunology, 2024)
This study explores critical subpopulations and their genetic alterations within peripheral blood mononuclear cells (PBMCs) using single-cell sequencing technology (scRNA-seq) in the context of severe acute pancreatitis (SAP). Initially, the study identifies a total of 20 distinct cell subtypes. Notably, a novel finding in this research is the identification of a specific monocyte subpopulation characterized by elevated expression of PF4 and PPBP.In comparison to healthy controls, SAP patients exhibit lymphocyte depletion, an increase in monocytes, and pronounced activation or upregulation of inflammatory pathways and genes. Particularly, the inflammatory pathways and receptor activation pathways related to monocytes are prominently affected. The study also elucidates the patterns of intercellular communication within these subpopulations.Lastly, Scissor is applied to identify cellular subpopulations associated with disease severity in PBMCs from the SAP single-cell dataset, guided by 87 large-sample acute pancreatitis whole transcriptome datasets with disease severity information. In summary, leveraging scRNA-seq, this study provides valuable insights into the roles and potential mechanisms of different cell subpopulations in SAP. Furthermore, it introduces a set of potential biomarkers with clinical significance for predicting the severity of SAP.